Biocatalytic metal–organic framework nanomotors for active water decontamination. Issue 94 (11th November 2020) - Guo, Ziyi; Liu, Jian; Li, Yong; McDonald, James A.; Bin Zulkifli, Muhammad Yazid; Khan, Stuart J.; Xie, Lei; Gu, Zi; Kong, Biao; Liang, Kang
Abstract : Biocatalytic metal–organic framework nanomotors for active removal of heavy metal ions and per- and poly-fluoroalkyl substances in aqueous environments. Abstract : We report a biocatalytic, buoyancy-propelled metal–organic framework (MOF) nanomotor system with boosted removal efficiency for both inorganic heavy metal ions and organic per- and poly-fluoroalkyl substances (PFAS). With the motion-induced convection and increased mass transfer of the target pollutants, the nano system exhibits excellent contaminants remediation capacity in both fresh water and sea water environments.